PENDIDIKAN KARAKTER (STUDI KOMPARASI PEMIKIRAN KH HASYIM ASY’ARI DAN KH AHMAD DAHLAN) IMPLEMENTASINYA DALAM PENDIDIKAN DI ERA GLOBAL - M.Ikhya’ul Ulum; Azhar Haq; Syamsu Madyan (VICRATINA, 2022)
This study aims to determine the problem of character education (Comparative Study of the Thinking of KH Hasyim Asy’ari and KH Ahmad Dahlan) it’s implementation in education in the global era. The problem faced is finding the moral attitude of a student who is not good, theoretically in terms of learning he is able to understand well, but in the process he is not able to carry out the theory well, like a child who is not educated in morals properly. This study uses the method used by the author is a qualitative descriptive approach and the type of research used is library research, namely collecting data or scientific writings that aim directly at the object of research or collection of library data. Data collection is done by collecting data from various journals and printed books which will then be analyzed again. After being analyzed, then these elements are combined again to reach a conclusion.